#TITLE_ALTERNATIVE# - AGUS (NIM 23306006); Pembimbing : Ir. Wisnu Hendradjit, M.Sc.E. dan Dr. Ir. Edi Leksono, M.En, LUKMAN
Energy efficiency is a part of operational requirements of building utilities. The study of chiller system operation in the computer building of the Finance Department of Indonesia is expected to present a picture concerning the optimization of chiller system operation which could improve its energy efficiency. In addition, the operation optimization could also maintain unit operation condition from early failure. The study of chiller system is performed by analyzing the chiller system operational procedures, electrical power factor, electrical power quality, chiller unit efficiency, chilled water pump operation efficiency, and cooling water pump operation efficiency. From the analysis of the chiller system operation, a few recommendations to optimize the chiller system operation entirely have been concluded. Some recommendations without investment capital were implemented in order to observe the achieved energy efficiency. Electrical system as the electrical power supply of the chiller system in the computer building has an undervoltage of 7,76%. The undervoltage on the cooling water pump has decreased pumping rate as large as 81,14 m3/hour as well as excessive electrical current of 5,25A in motor wound. From the study of electrical power factor of the chiller system, it has been founded that the lowest power factor is 0,72. By installing an artificial capacitive load of 59,43 kVA the power factor is maintained at 0,86. The effort would be able to eliminate disincentive bill introduced by the electric company which could reach Rp19.772.166,-/month. Chiller system operation optimization effort by shifting chiller system operation time could yield electrical power consumption efficiency of 14.44% from the consumtion before. Optimization effort by changing centrifugal pump impeller on the CWP installation could save 36% of CWP energy consumption or 6,84% of total energy consumption. In addition, it also keeping the chiller system from undergoing overpressure in the piping system. The recommendation which is applied in the chiller system operation is the control of chilled water and cooling water flow rate, and change of chiller unit operation time. By reducing chilled water and cooling water flow rate by 46m3/hour and 22.23m3/hour, respectively, as well as terminating the chiller unit operation at 17.00, electrical power consumption which is yielded is 56,506.87kVAh/month or 22.15% of the total electrical power consumption of the chiller system and air conditioner.